The reality and potential of renewable energies in Arab Maghreb countries: study the solar and water potential of Algeria, Tunisia, and Morocco using the principal component analysis (PCA) - zerrouki, Safia; sahli, Lazhar; bensalma, ahmed (Journal of Excellence for Economics and Management Research, 2023)
Energy security is a hot research topic these days because of its political, security and economic importance. With progress and economic growth, the demand for all types of energy is increasing, as is the pace of their consumption, and this is driving the search for and development of sustainable and clean energy sources. This paper aims to highlight renewable energy in its various forms and investigate the reality and potential of renewable energy sources in the Maghreb, focusing on solar and hydropower. The study produced a number of results, the most important of which was that the Maghreb countries have enormous solar and hydroelectric capacity. However, investment in these capabilities has been neither positive nor productive, resulting in no more than 5% of electricity being generated from these two sources in 2020.